(untitled) (International Journal of Engineering and Computer Science, 2015)
Data Center Infrastructure Management (DCIM) captures detailed real-time information about energy use across our data centers and operational facilities, enabling us to measure, trend, alert, and take action. DCIM also helps us visualize our data center environment in 3D and manages the power space and cooling capacity of your environment to better meet our business objectives. The baseline is being provided from the solution through which one can measure cost savings, improvements in operational reliability performance, cost savings as well as help to deliver continuous information for ongoing improvement. It enables data collection from multiple protocols and systems which further reduces manual efforts and thus provides visibility into power and space utilization, allowing for real-time decision making in a smart way. The proposed work utilizes dot net technologies to help us to perform the DCIM tasks. We have successfully deployed an application for the task and the report further signifies the importance of DCIM. The racks are visible in the network where and how they are connected which helps to monitor, and regulate their capacities improving cloud computing services of DCIM. We propose to develop state of the art technology and further initiate research and development work in cloud associated services.